2008
DOI: 10.1590/s0100-06832008000200038
|View full text |Cite
|
Sign up to set email alerts
|

Biomassa, decomposição e cobertura do solo ocasionada por resíduos culturais de três espécies vegetais na região centro-oeste do Brasil

Abstract: RESUMOCom a crescente adoção da semeadura direta na região Centro-Oeste do Brasil, faz-se necessário maior conhecimento sobre as plantas de cobertura para produção de palha. O presente estudo teve como objetivo avaliar a produção de biomassa verde e seca, a percentagem de cobertura do solo, bem como a dinâmica da decomposição da palhada de três espécies de plantas de cobertura em safrinha: amaranto (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
3
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 13 publications
(18 reference statements)
1
26
3
19
Order By: Relevance
“…Calvo et al (2010) reported a shoot dry matter production of 1,397 and 7,631 kg ha -1 of pigeonpea and of pigeonpea-pearl millet intercrop, respectively, 60 days after sowing, grown from March to July on a dystroferric Red Nitosol, in a conventional soil tillage system and with fertilization at planting of 200 kg ha -1 of N-P-K fertilizer 08-28-16. In regard to pearl millet, SDM production in this study was greater than the yields achieved by Boer et al (2007Boer et al ( , 2008 and Cazetta et al (2005), which were 10,801 and 10,673 kg ha -1 51 days after sowing and 60 DAE, respectively. It should be noted that Boer et al (2007Boer et al ( , 2008 sowed pearl millet in April on a dystroferric Red Oxisol with fertilization at sowing of 250 kg ha -1 of the N-P-K fertilizer 08-28-16.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Calvo et al (2010) reported a shoot dry matter production of 1,397 and 7,631 kg ha -1 of pigeonpea and of pigeonpea-pearl millet intercrop, respectively, 60 days after sowing, grown from March to July on a dystroferric Red Nitosol, in a conventional soil tillage system and with fertilization at planting of 200 kg ha -1 of N-P-K fertilizer 08-28-16. In regard to pearl millet, SDM production in this study was greater than the yields achieved by Boer et al (2007Boer et al ( , 2008 and Cazetta et al (2005), which were 10,801 and 10,673 kg ha -1 51 days after sowing and 60 DAE, respectively. It should be noted that Boer et al (2007Boer et al ( , 2008 sowed pearl millet in April on a dystroferric Red Oxisol with fertilization at sowing of 250 kg ha -1 of the N-P-K fertilizer 08-28-16.…”
Section: Resultscontrasting
confidence: 65%
“…In regard to pearl millet, SDM production in this study was greater than the yields achieved by Boer et al (2007Boer et al ( , 2008 and Cazetta et al (2005), which were 10,801 and 10,673 kg ha -1 51 days after sowing and 60 DAE, respectively. It should be noted that Boer et al (2007Boer et al ( , 2008 sowed pearl millet in April on a dystroferric Red Oxisol with fertilization at sowing of 250 kg ha -1 of the N-P-K fertilizer 08-28-16. Cazetta et al (2005) performed no-tillage sowing of pearl millet in September on a dystrophic Red Oxisol, with no fertilization at sowing.…”
Section: Resultscontrasting
confidence: 65%
“…To describe black oat decomposition, the data were fitted to an exponential mathematical model, previously described by Wieder & Lang (1982) and employed by Boer et al (2008), using the following equation: (-kt) ( 1) where P is the dry biomass quantity at time t (in days), Po is the fraction of potentially decomposable dry biomass, and k is the constant for dry biomass decomposition.…”
Section: Methodsmentioning
confidence: 99%
“…Contudo, especialmente nas regiões Sudeste e Centro-Oeste do Brasil, a produção e a manutenção de cobertura vegetal na superfície do solo é um desafio, devido ao inverno seco, que limita o cultivo nessa época, e o verão quente e chuvoso, que aceleram a decomposição da palhada (BOER et al, 2008;LEITE et al, 2010;SILVA et al, 2010). Assim, a quantidade e a durabilidade da fitomassa, bem como sua capacidade de reciclar nutriente, são características importantes a serem consideradas na escolha das plantas de cobertura (BOER et al, 2008;LEITE et al, 2010).…”
Section: Introductionunclassified
“…Entre as espécies utilizadas como plantas de cobertura e para adubação verde, duas se destacam: a crotalária (Crotalaria juncea L.), pela boa cobertura do solo proporcionado pelo rápido crescimento, pela associação simbiótica com bactérias fixadoras de N 2 (PERIN; GUERRA; TEIXEIRA, 2003) e supressão de nematóides parasitas (INOMOTO et al, 2008), sendo que essa última característica tem acarretado em grande expansão do cultivo dessa espécie nas áreas de produção de grãos na região do cerrado brasileiro; e o milheto (Pennisetum glaucum (L.) R. Brown), que é caracterizado pela produção de palhada em grande quantidade e com características de maior persistência sobre o solo (BOER et al, 2008;SILVA et al, 2010), pela alta capacidade de extração de nutrientes do solo, com amplas vantagens de reciclagem, principalmente N e K, reduzindo os riscos de lixiviação (ROSOLEM;PACE;CRUSCIOL, 2004;CRUSCIOL;SORATTO, 2007SORATTO, , 2009LEITE et al, 2010).…”
Section: Introductionunclassified